Cloning of hok gene into anhydrotetracycline inducible pASK75 vector reveals potent antimicrobial effect of 19 amino acid long N‐terminal fragment of hok peptide. (23rd October 2020) - Kaur, Anit; Muthukumarappa, Thungapathra; Kanta, Poonam; Banday, Aaqib Zaffar; Chidananda, Mohana Kumari
Abstract: An important toxin‐antitoxin (TA) system hok/sok, encoded by R1 plasmid of Escherichia coli, is involved in the post segregation killing of cells that have lost the plasmid. The lethal properties of hok protein have been utilized for the environmental containment of microbes and the development of potential vaccine candidates. This study aimed to demonstrate the potent anti‐microbial property of a 19 amino acid (AA) long N‐terminal fragment of hok peptide. This was accomplished by designing a conditional suicide system based on hok gene expression cloned in an anhydrotetracycline (aTc) inducible vector – pASK75. Heat shock and electroporation were utilized for the transformation of Escherichia coli and Vibrio cholerae cells, respectively. The minimal induction concentration (MId C) of aTc, determined by analyzing the expression of green fluorescent protein cloned separately into pASK75 vector, was 30 ng/mL. As hok gene was synthesized de novo (using recombinant polymerase chain reaction) in our study, various random sized hok fragments were generated (as a result of the error‐prone nature of Taq polymerase). The smallest hok fragment able to bring about effective antimicrobial killing was a 19 AA long N‐terminal fragment of hok having the wild type sequence, except for the carboxy terminus AA residue. The MId C of aTc in our experiments was 6‐fold lower than previously reported, making our bacterial clones suitable for use in mammalian systems as potential vaccine candidates. Based on our experiments, we hypothesize the 19 AA long N‐terminal fragment of hok peptide to be the smallest possible hok fragment sufficient to bring about effective antimicrobial killing.